Concrete Jungle: The Planetary Urbanization of the Ecuadorian Amazon. Issue 3 (November 2015) - Wilson, Japhy; Bayón, Manuel
This paper explores the possibilities and limitations of a post-neoliberal political project under conditions of planetary urbanization. We conceptualize planetary urbanization in terms of a tendency towards the real subsumption of space to capital on a global scale, through which capital is empowered as an abstract form of domination. We then relate this tendency to the ideology of 'systemic competitiveness' that has dominated the post-neoliberal project in Latin America, arguing that it threatens to strengthen the power of capital-as-subject. This relationship is illustrated by the Initiative for the Regional Infra-structural Integration of South America (IIRSA), and its incorporation into the post-neoliberal experiment currently underway in Ecuador. We focus on a series of IIRSA-related projects in the Ecuadorian Amazon, through which the real subsumption of space is disaggregated into three intertwined dimensions: territory, nature, and everyday life. In each case, we show how the ideological structure of post-neoliberalism unwittingly promotes the real subsumption of space and the empowerment of capital. However, the uneven dynamics of planetary urbanization imply that these projects are only succeeding in reproducing existing conditions of formal subsumption on an extended scale. The paper thus develops a materialist understanding of planetary urbanization in order to explain the failure of a political project to achieve its unintended results.